TRAFFIC FLOWS MODELLING BASED ON PROBABILITY OF COINCIDENCE OF CHAOTIC IMPULSES OF RANDOM DURATION AND RANDOM INTERVALS BETWEEN THEM - Levterov, A.; Левтеров, А. І.; Левтеров, А. И. (Харьковский национальный автомобильно-дорожный университет, 2017)
The features of applying the theory of chaotic electrical impulse flows in mathematical modelling of traffic flows have been considered. Both the moments of appearance of vehicles on the traffic lane and the moments of appearance of electrical impulse on the time axis are supposed to obey the Poisson law. It is assumed that the duration of an impulse is equivalent to the length of a vehicle, and the intervals between the impulses are equivalent to the intervals between the vehicles in the spatial-temporal axis.
МОДЕЛЮВАННЯ ТРАНСПОРТНИХ ПОТОКІВ НА ОСНОВІ ЙМОВІРНОСТІ ЗБІГУ ІМПУЛЬСІВ, ЩО ПРЯМУЮТЬ ХАОТИЧНО, ВИПАДКОВОЇ ТРИВАЛОСТІ Й ВИПАДКОВИХ ІНТЕРВАЛІВ МІЖ НИМИ
МОДЕЛИРОВАНИЕ ТРАНСПОРТНЫХ ПОТОКОВ НА ОСНОВЕ ВЕРОЯТНО-СТИ СОВПАДЕНИЯ ХАОТИЧНЫХ ИМПУЛЬСОВ СЛУЧАЙНОЙ ДЛИТЕЛЬ-НОСТИ И СЛУЧАЙНЫХ ИНТЕРВАЛОВ МЕЖДУ НИМИ
Keywords: traffic flow; chaotic electrical impulse flow; coincidence of impulses; транспортний потік; транспортний засіб; хаотичний електричний імпульсний потік; збігання транспортних засобів; транспортный поток; транспортное средство; хаотичный электрический импульсный поток; совпадение транспортных средств; 519.876.2:656:621.391.833